2001
DOI: 10.1161/hy1001.092614
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein and Soluble Fiber Reduce Ambulatory Blood Pressure in Treated Hypertensives

Abstract: Abstract-In population studies, higher blood pressure has been associated with lower intake of protein and, possibly, lower fiber consumption. In the present randomized controlled trial, we sought to determine whether dietary protein and fiber had additive effects on blood pressure reduction in hypertensives. Treated hypertensive patients changed for 4 weeks (familiarization) to a diet low in protein (12.5% energy) and fiber (15 g/d). Patients (nϭ41) were then randomized to 1 of 4 groups in an 8-week factorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
1
5

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(126 citation statements)
references
References 26 publications
4
116
1
5
Order By: Relevance
“…13 The Intersalt Study, a large cross-sectional international study with 10 020 men and women aged 20-59 years from 54 population-based samples in 32 countries worldwide, also demonstrated that total dietary protein intake had an inverse relationship with BP. 23 Similarly, Liu et al 22 concluded in a metaanalysis report that the inverse association between dietary protein intake and BP was quite convincing in nine population-based cross-sectional studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 The Intersalt Study, a large cross-sectional international study with 10 020 men and women aged 20-59 years from 54 population-based samples in 32 countries worldwide, also demonstrated that total dietary protein intake had an inverse relationship with BP. 23 Similarly, Liu et al 22 concluded in a metaanalysis report that the inverse association between dietary protein intake and BP was quite convincing in nine population-based cross-sectional studies.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15] However, it is unclear whether plant and animal proteins have different effects on BP.…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore likely that the higher protein intake in the high-protein diet was responsible for the attenuated rise in blood pressure. Observations from several large epidemiological studies [30,31] and short-term (6-13 week) clinical trials [32,33] have demonstrated that protein intake may be inversely related to blood pressure, although which component of dietary protein might be involved is unclear. The present data also support the hypothesis that a long-term higher protein intake may help to lower blood pressure and CVD risk in people with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous trials have used a refined carbohydrate as the control. [14][15][16]22 Limited data from human and animal studies suggest that a lupin-enriched diet may benefit serum lipids and lipoprotein. 24,49 However, we previously showed that an ad libitum lupin flour-enriched diet over 4 months also had no benefit on the serum lipid profile.…”
Section: At 4 Monthsmentioning
confidence: 99%
“…13 If consumption of lupin flour-enriched foods has similar effects on energy intake in the longer term, such effects could translate into weight loss. Diets higher in plant protein and fibre may also benefit blood pressure, [14][15][16][17] serum lipids 18,19 and glucose and insulin metabolism. 20,21 In a previous 16-week trial, we showed that consumption of lupin flour-enriched bread reduced 24-h systolic blood pressure by 3.0 mm Hg.…”
Section: Introductionmentioning
confidence: 99%